GENDER INJUSTICE AGAINST FEMALE CHARACTERS IN THE NOVEL LUKA PEREMPUAN ASAP BY NAFI'AH AL-MA'RAB - Agustriani; Roziah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The quality of women’s resources is a strategic issue that plays an important role in shaping social life and future generations. However, until now, women still face various forms of injustice due to the strong construction of patriarchal culture and unequal gender relations. Literature is an important medium to represent this reality as well as a means of social criticism. This study aims to examine the forms of gender injustice experienced by female characters in the novel Luka Perempuan Asap by Nafi’ah Al-Ma’rab through the perspective of feminist literary criticism. This research uses a qualitative approach with descriptive methods and literature. Data in the form of words, sentences, and paragraphs representing gender injustice were collected through intensive reading techniques and analyzed based on the framework of gender injustice Yulianeta (2021), which includes marginalization, domination, subordination, and repression. The results of the study showed that there were 20 data on gender injustice experienced by female figures, with subordination as the most dominant form, followed by domination, repression, and marginalization. The character of Mun as the main character experiences the most intense gender injustice, both in the family, education, and social realms. These findings confirm that the four forms of gender injustice are interrelated and form a structural system of oppression against women. The novelty of this research lies in the analysis of the relationship between forms of gender injustice as an ideological unit in the narrative of the novel. This research contributes to enriching the literary study of Indonesian feminism and increasing critical awareness of the issue of gender injustice through the reading of literary works.